Ecological Water Requirement Accounting of the Main Stream of the Yellow River From the Perspective of Habitat Conservation - Zhao, Fen; Li, Chunhui; Shang, Wenxiu; Zheng, Xiaokang; Wang, Xuan; Liu, Qiang; Bu, Jiuhe (Frontiers in Ecology and Evolution, 2022)
The Yellow River Basin is of great significance to China's economic and social development and ecological security. The Yellow River Basin is not only an important ecological barrier but also an important economic zone. In this paper, natural hydrological conditions were taken as a reference, a habitat simulation model of the key sections of the Yellow River was constructed based on the MIKE 21 model, and an ecological water requirement assessment method for river ecological integrity combined with habitat simulation and features of the hydrological reference group was established, which takes into account the survival and reproduction of indicator species. The suitable flow rates for the spawning period of Silurus lanzhouensis in Lanzhou and Xiaheyan and Cyprinus carpio in Toudaoguai, Longmen and Huayuankou were 350 - 720 m3/s, 350 - 600 m3/s, 150 - 500 m³/s, 260 - 400 m3/s, and 100 - 500 m³/s, respectively. Therefore, high pulse flow with a low flow peak should be guaranteed in mid- to late April. The peak flow should be at least approximately 1,000 m3/s to ensure that fish receive spawning signals, with a high pulse flow process occurring 1 - 2 times in May to June. The annual ecological water requirement of the Lanzhou, Xiaheyan, Toudaoguai, Longmen and Huayuankou sections was 9.1 - 11×109 m³, 6.3 - 10.4×109 m³, 3.8 - 8.2×109 m³, 4.7 - 11.3×109 m³ and 7.9 - 15.4×109 m³, respectively. The model quantitatively simulates the changes in ecological water requirement of indicator fishes in key sections of the Yellow River, and an effective and more realistic tool for ecological water requirement accounting of the Yellow River has been provided